Design and Implementation of a Lightweight Neural Controller for LLM Agent Systems (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Large language model (LLM) agents typically consume thousands of tokens on scaffolding system prompts, tool schemas, and conversation history before producing a single useful word. NEXUS (Neural EXecution & Understanding Substrate) is a 6.29-million-parameter neural controller that sits between a frozen LLM and its execution environment, replacing that token overhead with compact vector signals.The controller has five subsystems that run together (1) Protocol Cortex, which writes task descriptions directly into the LLM’s key-value cache so the model behaves as though it received detailed instructions without those instructions; (2) Belief Engine, a recurrent state-space model that tracks what the agent currently believes about its environment; (3) Resource Router, tool-selection classifier that uses explicit state-machine logic to guarantee valid tool calls; (4) Drift Sentinel, a lightweight monitor that detects when the agent’s output begins drifting off-task; and (5) Adapter Switch, which selects among small, low-rank weight updates (LoRA adapters) to specialize the LLM for different sub-tasks on the fly.We make three separate claims. First, we describe the architecture and the training recipe for all five components. Second, we report a deployment result: an open-source Model Context Protocol (MCP) server, nexus-mcp-oss, which achieves 72.86% fewer tokens delivered to the LLM in production through heuristic text-level compression (distinct from the KV-cache injection mechanism). Third, we present a controlled evaluation of the KV-cache injection mechanism itself, in which the Protocol Cortex is trained end-to-end with a frozen TinyLlama 1.1B and reaches a held-out perplexity of 8.91 versus 26,607 for an untrained baseline 2,987-fold improvement and 30–77 times lower perplexity than Prefix-Tuning, ActAdd, and LLMLingua at matched compression. Three of the four trained components converge on the synthetic benchmark; trained checkpoints, and benchmark data are publicly available. We are explicit about scope: the gains reported here are measured as token efficiency and predictive (perplexity) quality, and we set out in Sections 8.5 and 9.5 a concrete plan to test whether these efficiency gains carry through to downstream task quality: reasoning, planning, coding assistance, and multi-agent coordination.